Mene and Guachimanes: Toward a Geological Reading - Raquel Abend van Dalen (Catedral Tomada: Revista de Crítica Literaria Latinoamericana, 2022)
This article proposes a new reading of Venezuelan oil novels Mene and Guachimanes from the theoretical framework of geological writing. While literary criticism has focused on anthropocentric aspects of these novels, a geological analysis considers other factors within their narratives (non-human agency, materiality of bodies, and accumulation processes). I argue that reading these novels from this materialist perspective enables us to highlight substantial narrative elements in oil fiction that other readings have not adequately addressed, which has led to the literary devaluation of these petrofictions.